2022
DOI: 10.4314/rjmhs.v5i2.9
|View full text |Cite
|
Sign up to set email alerts
|

Nursing and Midwifery Students’ Perceptions and Experiences of Using Blended Learning in Rwanda: A Qualitative Study

Abstract: BackgroundAlthough blended learning (BL) is being adopted in public and private higher learning institutions (HLIs) in Rwanda, little is known about students’ use of BL in their learning activities. This article describes a qualitative descriptive study of students’ perceptions and experiences of BL in Rwanda’s post-secondary nursing and midwifery programs in public and private HLIs.MethodsThirty-three nursing and midwifery students from all public and private HLIs in Rwanda exposed to BL were invited to parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This study also revealed several challenges about digital technology utilization for clinical learning (Badowski et al, 2021;Bryan et al, 2022;Flo et al, 2021;Fung et al, 2021;Hu et al, 2022;Jiménez-Rodríguez & Arrogante, 2020;Kim et al, 2021;Mbombi et al, 2022;Ndayisenga et al, 2022;Oducado & Soriano, 2021;Saab et al, 2022;Yi et al, 2022). Technical challenges such as accessibility or usability issues and unavoidable technical difficulties were cited as impediments to the use of digital technology among undergraduate nursing students during the COVID -19 pandemic.…”
Section: Challenges Of Digital Technologymentioning
confidence: 81%
See 3 more Smart Citations
“…This study also revealed several challenges about digital technology utilization for clinical learning (Badowski et al, 2021;Bryan et al, 2022;Flo et al, 2021;Fung et al, 2021;Hu et al, 2022;Jiménez-Rodríguez & Arrogante, 2020;Kim et al, 2021;Mbombi et al, 2022;Ndayisenga et al, 2022;Oducado & Soriano, 2021;Saab et al, 2022;Yi et al, 2022). Technical challenges such as accessibility or usability issues and unavoidable technical difficulties were cited as impediments to the use of digital technology among undergraduate nursing students during the COVID -19 pandemic.…”
Section: Challenges Of Digital Technologymentioning
confidence: 81%
“…Four mixed method studies were conducted in the following countries: USA (n = 1) (Schiavenato et al, 2022), Norway (n = 1) (Flo et al, 2021), Spain (n = 1) (Jiménez-Rodríguez & Arrogante, 2020), Canada, England, Scotland and Australia (n = 1) (Goldsworthy et al, 2022). The ten qualitative studies were carried out in the USA (n = 2) (Abram et al, 2021;Badowski et al, 2021 ); Australia (n = 1) (Balante et al, 2023), Canada (n = 1) (Bryan et al, 2022), Hong Kong (n = 1) (Fung et al, 2021), Singapore (n=1) (Hu et al, 2022), Japan (n = 1) (Kazawa et al, 2022), Korea (n = 1) (Kim et al, 2021) and Rwanda (n = 1) (Ndayisenga et al, 2022). Four quantitative studies were conducted as follows: RSA (n = 1) (Mbombi et al, 2022), Philippines (n = 1) (Oducado & Soriano, 2021), Nepal (n = 1) (Thapa et al, 2021) and Spain (n = 1) (Zaragoza-García et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations